Genus-level taxonomical changes in the Lepanthes affinity (Orchidaceae, Pleurothallidinae) - Bogarín, Diego; Karremans, Adam P.; Fernández, Melania (Phytotaxa, 2018)
We propose a new classification of the Lepanthes affinity based on previous studies and our ongoing phylogenetic re-evaluation of the Pleurothallidinae. Fourteen genera are recognized as belonging to the affinity. They are found highly supported in a DNA-based phylogenetic inference of combined plastid (matK) and nuclear (nrITS) datasets. The necessary changes, including four novel generic concepts, needed to reorganize the Lepanthes affinity, are proposed here to insure monophyly. The integral discussion on the phylogenetics and biogeography of the group, together with morphological characterization of each clade will be presented in a follow up study.